2012
DOI: 10.2527/jas.2011-4237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early- to mid-gestational undernutrition with or without protein supplementation on offspring growth, carcass characteristics, and adipocyte size in beef cattle1

Abstract: Angus × Gelbvieh cows with 2 to 3 previous pregnancies were used to evaluate effects of maternal nutrient restriction on offspring adipose tissue morphology at standard production endpoints. At 45 d after AI to a single sire, pregnancy was confirmed and cows randomly allotted into groups and fed a control (Con, 100% of NRC recommendations), nutrient-restricted (NR, 70% of Con diet), or nutrient-restricted + protein-supplemented (NRP, 70% of Con + essential AA supply to the small intestine equal to Con) diet. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 40 publications
(46 reference statements)
5
61
0
1
Order By: Relevance
“…Thus, the nutritional regimens were instigated at exactly the same time points in gestation and were controlled with heifers being fed individually from 60 days before AI and throughout gestation until term. This is similar to previous fetal programming studies reported by (Sullivan et al 2009;Micke et al 2010a) but not others (Cafe et al 2006;Greenwood and Cafe 2007;Hickson et al 2008;Long et al 2009Long et al , 2012. Furthermore, in these latter three studies, realimentation of the restricted heifers was applied so that all calved at similar weight.…”
Section: Nutritional Interventionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, the nutritional regimens were instigated at exactly the same time points in gestation and were controlled with heifers being fed individually from 60 days before AI and throughout gestation until term. This is similar to previous fetal programming studies reported by (Sullivan et al 2009;Micke et al 2010a) but not others (Cafe et al 2006;Greenwood and Cafe 2007;Hickson et al 2008;Long et al 2009Long et al , 2012. Furthermore, in these latter three studies, realimentation of the restricted heifers was applied so that all calved at similar weight.…”
Section: Nutritional Interventionsupporting
confidence: 87%
“…It has previously been established that protein restriction in early gestation may affect post-natal reproduction and production traits in progeny (Sullivan et al 2009(Sullivan et al , 2010Micke et al 2010aMicke et al , 2011Mossa et al 2013). Further, studies have also shown effects of maternal diet upon fetal growth to 123 days post-conception (dpc) after dietary intervention 30-123dpc (Long et al 2009) although this effect was no longer apparent at birth (Long et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…78,79 In cattle, nutrient restriction of gestating cows resulted in heifer offspring with reduced wet ovarian weight and decreased luteal tissue mass compared with heifers born to control-fed cows. 80 Funston et al 81 also reported heifers born to cows that were protein-supplemented during the last one-third of pregnancy attained puberty 14 days earlier than heifers from nonsupplemented dams.…”
Section: Nutrition Optimization Of Pubertymentioning
confidence: 98%
“…Pathological conditions in pregnancy such maternal under nutrition, placental insufficiency, and diabetes have the potential to increase or decrease the delivery of carbohydrates to the fetus and adversely affect growth, body composition, and long term outcomes in human and livestock pregnancy [13,14]. For example, diabetic pregnancies are characterized by increased glucose transfer to the fetus with subsequent elevations in fetal insulin concentrations [15].…”
Section: Introductionmentioning
confidence: 99%